Ultrafast imaging of spontaneous symmetry breaking in a photoionized molecular system - Li, Min; Zhang, Ming; Vendrell, Oriol; Guo, Zhenning; Zhu, Qianru; Gao, Xiang; Cao, Lushuai; Guo, Keyu; Su, Qinqin; Cao, Wei; Luo, Siqiang; Yan, Jiaqing; et al. (Nature Communications, 2021)
The Jahn-Teller effect is an essential mechanism of spontaneous symmetry breaking in molecular and solid state systems, and has far-reaching consequences in many fields. Up to now, to directly image the onset of Jahn-Teller symmetry breaking remains unreached. Here we employ ultrafast ion-coincidence Coulomb explosion imaging with sub-10 fs resolution and unambiguously image the ultrafast dynamics of Jahn-Teller deformations of CH4+ cation in symmetry space. It is unraveled that the Jahn-Teller deformation from C-3v to C-2v geometries takes a characteristic time of 207 fs for this system. Classical and quantum molecular dynamics simulations agree well with the measurement, and reveal dynamics for the build-up of the C-2v structure involving complex revival process of multiple vibrational pathways of the CH4+ cation. The Jahn-Teller effect is the spontaneous symmetry breaking of the molecular structure caused by the coupling of electrons and nuclei. Here the authors use ultrafast Coulomb explosion imaging to map the evolution of the fundamental symmetry lowering process in photoionized methane within around 20fs.
Gesehen am 08.12.2021